1899 Wyo. Rev. Stat. 1252, div. 5, tit. 1, ch. 3, § 5050 - (:unkn) unknown (My University, 1899)
Whoever draws or threatens to use any pistol, dirk, knife, slung-shot, or any other deadly or dangerous weapon, already drawn, upon any other person, shall be fined in a sum not more than one hundred dollars, to which may be added imprisonment in the county jail not more than six months; Provided, That the provisions of this section shall not apply to a person drawing or threatening to use such dangerous or deadly weapon in defense of his person or property, or in defense of those entitled to his protection by law.
Keywords: BRANDISHING